Antifilarial potential of the root extract of the Mirabilis jalapa Linn. (Nyctaginaceae) on cattle filarial parasite Setaria cervi - Ahmed, Qamar Uddin; N, Parveen; Khan, Nizam U; SM Kashif, R Zaidi; Singal, KC (Springer, Springer Korea Limited, Seoul, Korea (Rep.)., 2003)
Effect of aqueous and alcoholic extracts of the roots of Mirabilis jalapa Linn. Four Oclock plant, onthe spontaneous movements of both the whole worm and the nerve-muscle (n.m.) preparation ofSetaria cervi and on the survival of microfilariae in vitro was studied. Alcoholic extract caused theinhibition of spontaneous movements of the whole worm and the n.m. preparation of S. cervi,whereas aqueous extract caused inhibition of spontaneous movements of the n.m. preparation.The initial stimulatory effect was not observed by aqueous and alcoholic extracts on n.m.preparation while effect of alcoholic extract on the whole worm was characterized by an increasein the amplitude of contractions followed by reversible paralysis. The concentrations required toinhibit the movements of the whole worm and n.m. preparation for alcoholic extract of root were270mg/mL and 40 mg/mL, respectively whereas an aqueous extract caused inhibition of n.m.preparation at 30 mg/mL suggesting a cuticular permeability barrier. Alcoholic extract of the rootsof M. jalapa caused concentration related effect on the survival of microfilariae of S. cervi. The LC50and LC90 for alcoholic extract as observed after 6 hrs. were found to be 10 ng/mL and 18 ng/mL.,respectively.